Editorial Introduction: Relocating East–West Migration and (Im)Mobilities - Russell King; Laura Moroşanu; Mari-Liis Jakobson; Garbi Schmidt; Md Farid Miah; Raivo Vetik; Jenny Money (Central and Eastern European Migration Review, 2022)
This introductory paper sets the scene for the special issue. It describes the rationale for the collection – which has to do with the multiple geopolitical, economic and health-related events of the past 30 years – and summarises some of the overarching changes in East–West migration dynamics within and beyond Europe over this period. However, this introductory article and the nine papers that follow also challenge and nuance the predominant East–West framing of recent intra-European migration. They identify numerous other trends: return migration and immigration into CEE countries, intra-CEE migrations and a range of issues relating to the impacts of migration on children and youth.